Culture of earthworm (Eisenia fetida), production, nutritive value and utilization of its meal in diet for Parachanna obscura fingerlings reared in captivity - VODOUNNOU, D.S.J.V.; KPOGUE, D.N.S.; MENSAH, GUY APOLLINAIRE; FIOGBE, EMILE DIDIER (My University, 2016)
The impact of the substitution of fish meal (FM) with earthworm meal (EM) in Parachanna obscura fingerlings diets was investigated for 42 days. Growth parameters, nutrient utilization and economical incidence of the fish were measured. Earthworms were cultured using animal wastes for 90 days and harvested, dried and stored. Five triplicate groups of fingerlings with initial average body weight of 1.13 ± 0.05g were respectively fed with earthworm meal containing 0, 25, 50, 75 and 100% isonitrogenous diet (45% crude protein). The fish were reared in 15 circular tanks which volume of 90 l each, at a density of 20 fingerlings per tank. Better growth rate and feed conversion efficiency were obtained with the fish’s diet containing 50% of earthworm meal. Feed efficiency, protein efficiency rate and specific growth rate between the groups of fish fed with 25% and 50% EM content diets were statistically similar (p>0.05).
Keywords: Earthworm meal; culture; growth performance; feed utilization and Parachanna obscura